Evaluation and external validation of minor lymphatic pelvic pathway for distant metastases in cervical cancer patients treated with concurrent chemoradiotherapy - Thephamongkhol K. (2023)
To evaluate and validate the minor lymphatic pathway for distant metastases in cervical cancer. This is a retrospective cohort of cervical cancer patients underwent curative concurrent chemoradiotherapy. We used original dataset from 1 university hospital and validation dataset from 3 university hospitals. Lymphadenopathy status in CT imaging was reviewed by radiologist in either the obturator and external iliac nodes (major pathway) or the internal iliac and presacral nodes (minor pathway). We then used Cox regression to adjust for all potential confounders, including paraaortic nodes, T stage, histology, age, total treatment time, total number of nodes, total short axis of nodes. 397 and 384 patients were in the original and validation datasets (median follow-up period, 59.5 month's). The minor pathway was independent prognostic factor in multivariable analysis [HR=2.64; 95%CI=1.07–6.55; P = 0.036] and [HR=14.84; 95%CI=3.15–70.01; P= 0.001] in original and validation datasets, respectively. Whereas, the major pathway was statistically non-significant. Further validation showed that the minor pathway had the highest HR for distant metastases with both the EMBRACE (HR=6.05; 95% CI=1.30–28.08; P = 0.022) and the FIGO 2018 (HR=7.43; 95% CI=2.94–18.78; P<0.001) in the original dataset. A similar result was found with the validation dataset: EMBRACE, HR=30.91; 95% CI=2.78–343.62; P = 0.005; and FIGO 2018, HR=42.41; 95% CI=8.83–203.60; P<0.001.This is the first clinical study to validate that the minor lymphatic pathway was predominantly associated with distant metastases in cervical cancer. This finding should be validated in larger cohort to further integrate in standard staging for prediction of distant metastases.